What Brings Gen-Z to the Library? An Investigation of Interior Design Elements in Denpasar City's Libraries - Anjaeni, Sharon Febrina; Hendrawan, Freddy; Dewi, Ni Made Emmi Nutrisia (Malikussaleh University, Aceh, Indonesia, 2025)
The development of technology and easier access to information have changed how Generation Z learns and interacts with their surroundings, including how they utilize library facilities. This study aims to analyze the factors influencing Generation Z's preferences in visiting libraries in Denpasar City, focusing on the interior design aspects of library spaces. The method used in this study is a descriptive qualitative approach, which involves observation, questionnaire distribution, and in-depth interviews with Generation Z students in Denpasar City. The results showed that interior design is crucial in attracting Generation Z's interest in visiting the Library. Libraries that carry a modern design concept, with adequate technological facilities to support learning and working activities, are more desirable than libraries that carry traditional concepts. Based on these findings, the proposed strategic solution is to implement the Modern Reading Hub concept, which combines ergonomic interior design, advanced technological facilities, and other supporting facilities. This concept is expected to create a library space that is more interactive, comfortable, and relevant to the needs of Generation Z in undergoing productive and fun learning activities.